The Effect of a Proposed Training Approach to Developing the Physiological Fitness fo The Heart and Circulatory System and the Performance of Quick Shooting Skills in Young Basketball Players - Munadi, Mohammad Jabbar (JURNAL PENDIDIKAN OLAHRAGA, 2025)
The lack of emphasis on endurance-specific training in junior basketball coaching often leads to early fatigue and suboptimal skill development during competition. This study aimed to develop and evaluate a structured training program designed to enhance special endurance and improve quick shooting performance among junior basketball players. An experimental method was employed involving 20 players aged 15–16 years from the Dhi Qar Governorate team, who were purposively selected and randomly assigned to either an experimental group or a control group (n = 10 each). The experimental group underwent a six-week intervention comprising 24 training sessions focused on cardiovascular endurance, while the control group followed their regular training routine. Pre- and post-tests measured performance using the Six-Time Rapid Layup Test and the Carlson Fatigue Curve Test. The experimental group showed a statistically significant improvement in layup performance (pre-test M = 50.79s, post-test M = 45.50s; t = 18.78, p < 0.05) and cardiovascular endurance (pre-test M = 20.2, post-test M = 9.8; t = 26.5, p < 0.05). In contrast, the control group showed only modest gains. These findings highlight the effectiveness of targeted endurance training in enhancing both physiological fitness and technical skill. It is recommended that basketball coaches integrate evidence-based endurance programs into junior training curricula to build physical resilience and support sustained athletic performance.